Exploring the Implicit Link Between Red and Aggressiveness as Well as Blue and Agreeableness - Geng, Lu; Hong, Xiaobin; Zhou, Yulan (Frontiers in Psychology, 2021)
Previous studies have found a link between red and aggressive behavior. For example, athletes who wear red uniforms in sports are considered to have a competitive advantage. So far, most previous studies have adopted self-report methods, which have low face validity and were easily influenced by the social expectations. Therefore, the study used two implicit methods to further explore the association between red and aggressiveness. A modified Stroop task was used in Experiment 1 to probe college students’ differences between “congruent” tasks (i.e., red–aggressiveness and blue–agreeableness) and “incogruent” tasks (i.e., red–agreeableness and blue–aggressiveness). Result showed that participants responded more quickly to the congruent tasks than the incongruent tasks. Then, in order to adapt to the competitive context, Experiment 2 used an implicit association test with photos of athletes as the stimulus to college students and athletes to evaluate “congruent” tasks (i.e., red uniform photo–aggressiveness and blue uniform photo–agreeableness) as well as “incongruent” tasks (i.e., red uniform photo–agreeableness and blue uniform photo–aggressiveness) respectively. According to the results, both college students and athletes respond faster to congruent tasks than to incongruent tasks. Besides, athletes’ reactions to the red-aggressiveness association are faster than college students, which may relate to the athletes’ professional experience. The athletes may be more aggressive and impulsive. Overall, the study has attempted to examine the association between red and aggressiveness through implicit methods, but in the future, researches are need to find a deep association from brain mechanism aspect.